Faktor yang mempengaruhi Nilai Perusahaan - PUTRI DYENTA NURCHOLIFAH (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This study examines the effect of company size, liquidity, profitability, leverage and asset structure on company value in manufacturing companies listed on the Indonesian stock exchange in 2019-2021. Firm size is measured using ln total assets, liquidity is measured using the current ratio, profitability is measured using NPM, leverage is measured using DER, asset structure is measured using current assets to total assets and company value is measured using PBV. the sampling method uses purposive sampling with the 2019-2021 research period. This study uses secondary data. the relationship and influence between variables is explained by using the t test method. The research results show that firm size, liquidity and asset structure have no significant effect on firm value. while profitability and leverage have a significant effect on firm value